Kontestasi dan Negosiasi Kepentingan dalam Implementasi Sistem Siaran Jaringan Televisi di Indonesia - Ade Armando (Jurnal Komunikasi, 2019)
This paper intends to show that the explanation for the failure of the private television network broadcast system in Indonesia --which was actually mandated in the 2002 Broadcasting Law – lies not in one single determinant factor but should be seen in the perspective of power relations that mutually constitute the arrangement of communication resources in Indonesia. Based on the experience of 17 years of the Broadcasting Law, there were four parties involved in the contestation and negotiations on the implementation of SSJ: private stations owners, government, parliament (DPR) and Indonesian Broadcasting Commission (KPI). Among all the contesting groups, the association of ten giant national television station is the most consistent gorup in pusuing their own specific interests. The owners of the private national television stations persistently tried to thwart the implementation of the SSJ. On the other hand, the other three camps continuously show different approach and attitude toward the issue, which reflect its ever changing context and actors involved in its institutions. Keywords: Television Network System, Indonesian Broadcasting Law 2002, Association of Private Television Stations, Ministry of Communication and Information, Indonesian Broadcasting Commission